How the Implementation of Children's Literature Favors the Development of English Language Comprehension (2023)
ABSTRACT: This research project report has as a purpose to describe the way children's literature favors the English comprehension in a fourth-grade class at educational institution La Marcelina in the municipality of Itagui. Data were collected through the research journal, a teacher's interview, and a focus group address to the students. These instruments were analyzed, coding and categorized in order to give the general findings. These findings show that the use of children's literature favors the English comprehension of the students, because they through children’s literature apply different activities that help them to improve their knowledge in English and consequently, they raise their English comprehension. It is reflected in the participation of class and in the development of the activities like reading aloud, checking for comprehension, and rewriting their own stories.